Transrectal ultrasound‐guided prostate biopsy in Taiwan: A nationwide database study. Issue 11 (November 2015) - Wei, Tzu‐Chun; Lin, Tzu‐Ping; Chang, Yen‐Hwa; Chen, Tzeng‐Ji; Lin, Alex T.L.; Chen, Kuang‐Kuo
Abstract : Background : For patients with an elevated prostate specific antigen (PSA) level or a suspected lesion detected by digital rectal examination, transrectal ultrasound‐guided (TRUS) prostate biopsy is the standard procedure for prostate cancer diagnoses. In Taiwan, TRUS prostate biopsy has not been well‐studied on a nationwide scale. This article aimed to study TRUS prostate biopsy in Taiwan and its related complications, according to the claims generated through the National Health Insurance (NHI) program. Methods : We applied for access to claims from the NHI Research Database of Taiwan of all patients who visited the urology clinic during the period of 2006 to 2010. In the 5‐year urology profile, we obtained all records, which included admission and ambulatory clinical records. The definition of TRUS biopsy included codes for ultrasound‐guided procedure and for prostate puncture; other codes involving complications such as postbiopsy voiding difficulty, significant bleeding, or infection requiring treatment were also included. Risk factors included age, diagnosis of prostate cancer, hospitalization or nonhospitalization, and the Charlson Comorbidity Index (CCI; with a value of 0, 1, 2 or ≥ 3). Descriptive and comparative analyses were also performed. Results : In the 5‐year urology profile, 12, 968 TRUS biopsies performed of which 6885 were in‐patient procedures and 6083 were ambulatory clinic procedures. After the procedures, 1266 (9.76%) biopsies were associated with voiding difficulty; 148 (1.14%) biopsies, with significant bleeding; and 855 (6.59%) biopsies, with infection that required treatment. The prostate cancer diagnosis rate was 36.02%. The overall biopsy‐related mortality rate within 30 days was 0.25%, and the postbiopsy sepsis‐related mortality rate was 0.13%. Age, diagnosis of cancer, hospitalization, and CCI value ≥ 1 were all significant factors in univariate analysis and multivariate analysis for postbiopsy voiding difficulty and severe infection. A diagnosis of cancer and a CCI value ≥ 2 were significant factors for significant bleeding after biopsy. Patients diagnosed as having prostate cancer had fewer bleeding complications after biopsy. Conclusion : The most frequent complication was postbiopsy voiding difficulty, followed by infection that required treatment and significant bleeding. The sepsis‐related mortality rate was 0.13%. Significant risk factors for postbiopsy complications included age, diagnosis of prostate cancer, hospitalization, and the CCI value.